Sloterdijk, Agamben y Nietzsche: biopolítica, posthumanismo y biopoder - Vásquez Rocca, Adolfo (Nómadas. Critical Journal of Social and Juridical Science, 2009)
Sloterdijk and Agamben agree on the importance of rethinking humanism (especially the conflict between human and animal) and locating Nietzsche in the epicenter of this problem. Sloterdijk traces the Nietzschean conception of man to find his early background in Plato (politician), particularly in the concepts of breeding and Dressage to Nietzsche's own use. To understand the scope of the topic will require defining what is meant by humanism and to what extent can we speak of a failure of it.
Keywords: Biopolitics; Bare life; 'Homo sacer'; Agamben; Human; Animal; Nietzsche; Education; Sloterdijk; Human Park; Poshumanismo; Politics